PROGRESSIVE LAW IMPLEMENTATION IN FALL ADDITIONAL CRIMINAL ON ITE CRIMINAL ACTIONS - Hendhy Eka Chandra; Hedwig Adianto Mau; Marsudin Nainggolan (Scholar Express Journals, 2023)
The imperfection of the rule of law gives Judges the room to make legal discoveries ( rechtvinding ) and to form laws (judge made law) through their decisions by exploring the values that live in society as required by the provisions of Article 5 paragraph (1) of Law of the Republic of Indonesia Number 48 of 2009 concerning Judicial Power. This research aims to assess whether the Decision of Pandeglang District Court Number 71/ Pid.Sus /2023/PN Pdl which imposes additional punishment of deprivation of certain rights can be called a progressive character decision. The method used in this research is normative juridical with statute approach and case approach. The results of this research show that the judge has expanded the punishment for ITE criminal offenses by imposing additional punishment in addition to the main punishment, which is actually unknown in the ITE Law regime, so that the decision can be called to have a progressive legal characters .
Keywords: information and electronic transactions; progressive law and criminal offenses